Pengaruh Store Atmosphere, Persepsi Harga, Word of Mouth, dan Gaya Hidup terhadap Keputusan Pembelian Konsumen Coffee Shop Kazoku Desa Sei Rakyat Labuhanbatu - Ridha Annisya; Pitriyani Pitriyani; Siti Lamaah Nasution (Jurnal Publikasi Ilmu Manajemen, 2026)
The increasingly intense commercial competition among coffee shops necessitates an understanding of the factors that influence customers’ purchasing decisions. This study aims to analyze the effects of store atmosphere, price perception, word-of-mouth (WOM) communication, and lifestyle on customers’ purchase intentions at Kazoku Coffee Shop in Sei Rakyat Village, Labuhanbatu. A quantitative approach was employed, involving 80 respondents selected through judgmental sampling. Data were collected by distributing questionnaires and were analyzed using SPSS version 22. The findings show that all research instruments were valid and reliable, and that the regression model satisfied the classical assumptions. Simultaneously, the four variables had a positive and significant effect on purchasing decisions, as indicated by an F-statistic of 248.396 and a significance value of 0.000. The coefficient of determination (R²) of 0.930 indicates that 93.0% of the variation in purchasing decisions is explained by the four variables, while the remaining 7.0% is influenced by factors beyond the scope of this study.